2020
DOI: 10.1017/s1047951120001626
|View full text |Cite
|
Sign up to set email alerts
|

Implementing standard screening for autism spectrum disorder in CHD

Abstract: Introduction: While the overall prevalence of autism is 1.7% in the United States of America, research has demonstrated a two- to five-fold increase in CHD. The Cardiac Neurodevelopmental Outcome Collaborative recommends screening for autism from infancy through adolescence. This study investigated the frequency of autism concerns at a single Cardiac Neurodevelopmental Program and examined current clinical practice as a way to improve quality of care. Materials and methods: Patients (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…This is higher than rates reported in a national sample of youth with CHD based on parent report (10.3%; odds ratio 1.6), 8 though it is very similar to studies using more rigorous clinical methods (e.g., 17.8-44% in studies using rating scales; 10-13 16-34% in studies using diagnostic interviews [15][16][17] ). Research generally suggests rates of autism are higher in children with CHD (2.6% based on parent report, 8 3.2% based on parent ratings, 19 5.9% based on diagnostic evaluation 20 ), and our results demonstrated even higher rates of autism (9.7%; odds ratio 4.37). Taken together, this pattern of results suggests more rigorous diagnostic methods (i.e., neurodevelopmental or neuropsychological evaluation) are necessary to appropriately identify children with autism or attentional disorders and supports previous assertions that regular evaluation, and not screening, is necessary for children with CHD.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…This is higher than rates reported in a national sample of youth with CHD based on parent report (10.3%; odds ratio 1.6), 8 though it is very similar to studies using more rigorous clinical methods (e.g., 17.8-44% in studies using rating scales; 10-13 16-34% in studies using diagnostic interviews [15][16][17] ). Research generally suggests rates of autism are higher in children with CHD (2.6% based on parent report, 8 3.2% based on parent ratings, 19 5.9% based on diagnostic evaluation 20 ), and our results demonstrated even higher rates of autism (9.7%; odds ratio 4.37). Taken together, this pattern of results suggests more rigorous diagnostic methods (i.e., neurodevelopmental or neuropsychological evaluation) are necessary to appropriately identify children with autism or attentional disorders and supports previous assertions that regular evaluation, and not screening, is necessary for children with CHD.…”
Section: Discussionsupporting
confidence: 50%
“…Research to date has shown that rates of neurodevelopmental disorders, including attentiondeficit/hyperactivity disorder, autism spectrum disorder (autism), and intellectual disability, are higher in children with CHD when compared to the general population. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Rates of attention-deficit/hyperactivity disorder are consistently higher in youth with CHD when compared to healthy controls; however, existing studies rarely utilise comprehensive clinical assessment. Methodologies vary but researchers typically use screening/parent report methods or focus on specific subsets of children with CHD considered to be at highest risk, resulting…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most care pathways (14 out of 22) were established between 2010 and 2015 and located in the USA (14 out of 22). They were most frequently found in children's hospitals (15 out of 22), with four provided across multiple health‐care settings 35,47,50,53 . Almost three‐quarters (16 out of 22) had a centralized service structure, with families required to travel to a specific tertiary‐level clinic to receive care.…”
Section: Resultsmentioning
confidence: 99%
“…Alam et al 35 Children started new speech therapy (50%), occupational therapy (56%), or physical therapy (50%) as a result of attending the neurodevelopmental follow-up programme; 31% of children developed new school plans and 86% of struggling students improved grades Tan et al 47 Children received a new autism diagnosis (n = 2) or referral to autism specialist (n = 9) as a result of neuropsychological evaluation in the follow-up programme Ruehl et al 33 The follow-up programme supported 97% of children who required new or expanded education plans to achieve these. For those in the programme, 96% of children improved in at least one area of school performance recommendations.…”
Section: Reported Outcomementioning
confidence: 99%